Kant a dějiny metafyziky - Karásek, Jindřich (Filosoﬁcký časopis)
The author of this paper focuses on an interpretation of Kant’s conception of the history of metaphysics as being a history of pure reason. Kant develops this conception both in the Critique of Pure Reason and in a later work in response to a question commissioned by the Royal Academy of Sciences: What advances has metaphysics made in Germany since the time of Leibniz and Wolff? Key passages in these writings will be given analytical attention. It will thus be shown that Kant’s purpose was not to eliminate metaphysics, but to correct it, and especially in his work On the Progress of Metaphysics, the philosopher from Königsberg points out the importance of skepticism within the history of metaphysics.